2018
DOI: 10.1136/bcr-2018-224350
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory failure caused by lipoid pneumonia from vaping e-cigarettes

Abstract: A young female vaper presented with insidious onset cough, progressive dyspnoea on exertion, fever, night sweats and was in respiratory failure when admitted to hospital. Clinical examination was unremarkable. Haematological tests revealed only thrombocytopenia, which was long standing, and her biochemical and inflammatory markers were normal. Chest radiograph and high-resolution CT showed diffuse ground-glass infiltrates with reticulation. She was initially treated with empirical steroids and there was improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
11

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 12 publications
4
94
0
11
Order By: Relevance
“…Meanwhile, to our knowledge, no well‐documented case of ELP with biopsy confirmation within the setting of EVALI has been published to date. Only a single case report based on a video‐assisted thoracoscopic surgical biopsy often is cited as demonstrating ELP attributed to vaping vegetable glycerin, but a review of the published photomicrograph revealed only cholesterol clefts (a nonspecific finding related to obstruction) lacking the characteristic ELP airspace macrophages with enlarged intracytoplasmic vacuoles or interstitial lipid deposits. In clinical reports of EVALI labeled as “lipoid pneumonia,” there was no histopathologic confirmation of ELP .…”
Section: Cytomorphologic Features In Cases Of Confirmed and Probable mentioning
confidence: 99%
“…Meanwhile, to our knowledge, no well‐documented case of ELP with biopsy confirmation within the setting of EVALI has been published to date. Only a single case report based on a video‐assisted thoracoscopic surgical biopsy often is cited as demonstrating ELP attributed to vaping vegetable glycerin, but a review of the published photomicrograph revealed only cholesterol clefts (a nonspecific finding related to obstruction) lacking the characteristic ELP airspace macrophages with enlarged intracytoplasmic vacuoles or interstitial lipid deposits. In clinical reports of EVALI labeled as “lipoid pneumonia,” there was no histopathologic confirmation of ELP .…”
Section: Cytomorphologic Features In Cases Of Confirmed and Probable mentioning
confidence: 99%
“…Exposure to certain electronic nicotine delivery systems (ENDS) cartridges has recently increased hospitalizations due to respiratory failure [68,13,14]. According to case reports since 2012, e-cig users with symptoms without direct etiology have undergone various diagnoses, including acute lung injury, atypical pneumonitis, and eosinophilic or lipoid pneumonia [6,13]. The presence of abnormal lipid-laden macrophages in lung tissue samples from EVALI subjects has been associated with lipoid pneumonia [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…However, vitamin E acetate has been found in bronchoalveolar lavage fluid (BALF) of EVALI patients [5]. Most of the subsequent analyses have been geared towards the constituents of e-liquids like Vitamin-E acetate (VEA) as implicated in these ENDS-user subjects [68]. There is an urgent need for experimental-based studies to implicate the causative role of VEA in EVALI or other lung conditions reported.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchoscopy and bronchoalveolar lavage have yielded variable results, with variable leucocytosis, no eosinophilia, and often 'foamy' or lipid-laden macrophages (positive O red or Sudan staining), which has led to the suggestion of 'lipoid pneumonia' changes (Viswam et al, 2018;Layden et al, 2019;Lewis et al, 2019;Maddock et al, 2019;Dicpinigaitis et al, 2020). However, the significance of this is controversial.…”
Section: Clinical Featuresmentioning
confidence: 99%